PENGGUNAAN MEDIA CETAK DALAM PEMBELAJARAN SENI BUDAYA MATERI MENGGAMBAR UNTUK MENINGKATKAN MINAT DAN KEAKTIFAN SISWA KELAS III SD - Qomariyah, Ryzca Siti; Khotimah, Husnul (Jurnal Likhitaprajna, 2019)
This study aims to increase the interest and active learning of students in learning Cultural Arts by using learning media (Print Media). This type of research was a Classroom Action Research conducted in 2 cycles as for the stages in conducting research this includes the stages of planning, implementing actions, observing, and reflecting. The instrument of this study are: (1) observation, (2) interview, and (3) test. The result of study showed that In the pre-action interest and student learning activeness was still not visible in the Art and Culture lesson at the first meeting of cycle I. Student learning activeness began to increase, Based on the results of the first cycle of the second meeting above it was found that 4 students (40%) students' interest and activeness began to increase. Whereas 6 students (60%) interest and activeness have not increased. Students who are interested and active in learning already have a minimum completeness criteria of 80%. So that students' learning completeness is good for the first cycle, but it needs to be improved from the first cycle which is to continue to the second cycle. Based on the interest and activeness of cycle II, it is known that 8 students (80%) are interested and active in learning in both categories. Whereas 2 students (20%) lacked in increasing interest and active learning because these students felt bored and fed up in learning mathematics. Students who are interested and active in the learning and learning process can get a minimum completeness standard of 80%. Keywords: Interest, Learning activeness, Learning Media (Print Media), Cultural Arts.